Investigation of process factors affecting mechanical properties of INCONEL 718 superalloy in wire plus arc additive manufacture process - Xu, Xiangfang; Ding, Jialuo; Ganguly, Supriyo; Williams, Stewart W. (Elsevier, 2018)
This paper systematically evaluated the effect of oxide, wire source and heat treatment on the mechanical properties of wire + arc additively manufactured (WAAM) INCONEL 718. Comparison of the as deposited grain structure was made with laser-powder based AM and wrought INCONEL 718. Results showed that oxides formed during deposition had no effect on the mechanical properties since a 0.5μm thick passivation layer consisting of Cr2O3 and Al2O3 formed upon deposition and prevented further oxides from forming inside the bulk. Wires from different suppliers resulted in around 50 MPa difference in UTS possibly due to the slight compositional variation and uncertainties in TiN inclusion. Standard heat treatment improved the strength from 824 MPa to 1110 MPa in the horizontal direction, but the average strength was 105 MPa lower than the wrought alloy. The as deposited WAAM INCONEL718 featured large columnar grains and numerous Laves phase, as compared to the fine grains of laser powder bed fusion and wrought INCONEL 718. This starting microstructure led to less favourable and less numerous precipitates forming during heat treatment, which is the main reason for the strength mismatch. A different heat treatment would not help due to the starting microstructure.
Keywords: INCONEL 718; Wire plus arc additive manufacture; Mechanical properties; Heat treatment; Oxide